2009
DOI: 10.1007/s11010-009-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder membrane permeability differentially induced by membrane lipid composition

Abstract: The permeability barrier of the urothelium (covering the mammalian urinary tract) has stimulated interest in the role of the luminal membrane in the barrier function. To know how membrane lipids may affect the permeability barrier we prepare endocytic vesicles of different lipid composition entrapping a fluorescent dye (HPTS) and its quencher (DPX) using a dietary strategy (rats fed with commercial, oleic acid- or linoleic acid-enriched diets) followed by endocytosis induction. Vesicular leakage was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 20 publications
3
26
1
Order By: Relevance
“…We also observed topological alterations of the urothelial plaques: the association between uroplakin dimers (Bongiovanni et al 2005) and the surface topography of urothelial particles was dependent on membrane lipid composition (Calderón and Grasso 2006). Moreover, we observed that the lipid composition also had an effect on the vesicle membrane permeability, describing for the first time the cytosolic leakage of endocytic vesicles content (Grasso and Calderón 2009). Besides, urothelial V-ATPase activity was modulated by the membrane lipid composition (Grasso et al 2011a).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…We also observed topological alterations of the urothelial plaques: the association between uroplakin dimers (Bongiovanni et al 2005) and the surface topography of urothelial particles was dependent on membrane lipid composition (Calderón and Grasso 2006). Moreover, we observed that the lipid composition also had an effect on the vesicle membrane permeability, describing for the first time the cytosolic leakage of endocytic vesicles content (Grasso and Calderón 2009). Besides, urothelial V-ATPase activity was modulated by the membrane lipid composition (Grasso et al 2011a).…”
Section: Introductionmentioning
confidence: 63%
“…The disrupted tissue was layered over a 1.6 M sucrose cushion (Chang et al 1994;Grasso and Calderón 2009) and centrifuged at 28,0009g at 4°C for 20 min in an L5-50B Beckman Ultracentrifuge. The vesicle-enriched fraction was collected at the water-sucrose interface and immediately assayed (SLM-Aminco spectrofluorometer).…”
Section: Vesicle Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to controls, oleic acid-derived superficial UCs have been shown to display decreased endocytosis of fluid and membrane-bound probes by 32% and 49%, respectively (Grasso and Calderon 2013). In addition to altered intracellular vesicle trafficking, endocytosed vesicles are capable of releasing their content, and the lipid membrane composition can affect the degree of leakage into the cytoplasm (Grasso and Calderon 2009). Superficial UC plasma membranes, with their urothelial plaques and rigidified lipids, should maximally prevent leakage of toxic urine substances into their cytoplasm, and apical endosomes do indeed exhibit very low (b) Expression and localization of UPs (anti-AUM, green) in porcine UCs in vitro cultured as is described in Višnjar and Kreft (2015).…”
Section: Membrane Lipid Compositionmentioning
confidence: 99%
“…The transcellular pathway consists of the apical and basolateral plasma membranes. The main transcellular permeability barrier is the apical plasma membrane of superficial UCs, which is unique in its many specialized features, such as its superficial glycosaminoglycan layer (Parsons 2007), urothelial plaques composed of transmembrane proteins uroplakins (Hu et al 2000;Kreft and Robenek 2012), and its particular lipid composition (Grasso and Calderon 2009), which all influence the course of passive diffusion, active transport, and endocytosis. The paracellular pathway consists of intercellular space and TJs, which are extremely impenetrable and represent the main barrier to paracellular transport (Fig.…”
mentioning
confidence: 99%